Congenital cytomegalovirus infection in Malaysia: a scoping review, clinical insights and future directions - Abu Bakar, Asrar; Wan Mahmud Sabri, Wan Muhammad Najib; Ali Hanafiah, Nurlin; Ahmad Fazli, Nurfarisha; Tan, Ciang Sang; Shunmugarajoo, Haema; Nik Yusoff, Nik Khairuddin (Penerbit Universiti Sains Malaysia, 2025)
Congenital cytomegalovirus (cCMV) infection is the most common congenital infection worldwide, greatly contributing to neonatal morbidity and long-term neurological and audiological complications. Despite its clinical burden, cCMV remains underdiagnosed in Malaysia due to the absence of routine screening programmes and limited awareness among healthcare professionals. This review presents an overview of the epidemiology, clinical manifestations, diagnostic approaches, and management strategies of cCMV in Malaysia, highlighting gaps in current practices and potential future approaches. The seroprevalence of cytomegalovirus (CMV) among pregnant women in Malaysia is high, with reported maternal seropositivity rates between 74% and 84%. However, cCMV incidence remains poorly defined due to the lack of systematic screening. Clinical features range from asymptomatic infection to severe neurodevelopmental impairments, sensorineural hearing loss, and visual deficits. Current diagnostic methods rely on polymerase chain reaction (PCR)-based detection of CMV DNA from urine, saliva, or blood within the first three weeks of life. However, access to molecular testing is limited. Treatment with antiviral agents such as valganciclovir can improve neurodevelopmental outcomes, particularly in symptomatic infants, but remains underutilised due to cost and availability constraints. Emerging research on rapid antigen-based diagnostics and maternal antiviral prophylaxis offers opportunities for improving early detection and intervention. Future strategies should focus on increasing awareness among healthcare providers, implementing targeted or universal newborn screening, and promoting research on cost-effective diagnostic and treatment modalities. Strengthening national policies and integrating cCMV management into existing maternal and child health programmes is vital to mitigate its long-term impact